Knowledge assessment of candidates in liver transplant - Oliveira, Priscilla Caroliny de (2017)
Aim: to verify the internal consistency of an evaluative knowledge questionnaire on the liver transplant process and evaluate the knowledge of the candidates on the waiting list for liver transplantation, as well as their perception of their own knowledge. Method: quantitative, descriptive / exploratory study, with patients on the waiting list for liver transplantation as participants. Results: Sixty-two patients constituted the sample, average queue time of 5.7 years. The mean score on the questionnaire was 7.4 with a standard deviation of 2.5. Questions related to the post-transplant stage showed the worst hit rates. Forty-three percent of the patients indicated that they received information about the disease and 77.4% did not consider those information sufficient. Regarding the understanding of the disease and transplantation, 37.1% and 45.2% showed insufficient understanding, respectively. The internal consistency of the questionnaire, verified by Cronbach's alpha, was 0.813. Conclusion: the questionnaire presented internal consistency to assess the candidate's' knowledge of a liver transplant and showed information deficit regarding the postoperative period of transplantation.